A rare case report of Ellis Van Creveld syndrome in an Indian patient and literature review - Prashanth Shetty; Deepthi Shetty; P.S. Priyadarshana; Smitha Bhat (Elsevier, 2015)
Ellis Van Creveld syndrome (EVC) is a rare genetic disorder having autosomal recessive inheritance affecting the Amish population of Pennsylvania in USA with incidence of 1:244,000 for the general population. This syndrome consists of characteristic features such as bilateral postaxial polydactyly, chondroectodermal dysplasia, congenital heart defects and hypoplastic nails and teeth. There are few case reports of this syndrome reported in dental literature. We report a case of a 17 year old female presenting typical features of this syndrome and the oral findings of this patient which are the key diagnostic features.